Perlindungan Hukum Terhadap Pihak Yang Dirugikan Dalam Perjanjian Tidak Tertulis - H Yasir; Rizky Perdana Bayu Putra; Dedi Dores (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the forms of legal protection for parties disadvantaged in unwritten agreements (oral contracts), which remain widely practiced in Indonesian society due to factors such as trust, simplicity, and cultural habits of informal transactions. Despite their prevalence, unwritten agreements often create vulnerabilities when disputes arise, as the absence of written documentation complicates the process of proving rights and obligations in legal proceedings. The study adopts a normative juridical approach combined with empirical data collection through interviews and case analysis to understand how such agreements are treated in practice. Findings indicate that while Article 1320 of the Indonesian Civil Code recognizes the validity of oral agreements as long as they meet essential legal requirements—consent, capacity, a specific object, and lawful cause—the practical enforcement faces challenges. Courts often encounter difficulties due to the weak evidentiary value of oral testimony compared to written contracts. Legal protection for disadvantaged parties is predominantly repressive, realized through litigation mechanisms (civil lawsuits) and non-litigation pathways such as mediation and arbitration. However, preventive legal protection is still limited, as public awareness of legal risks and the use of written or digital contracts remains relatively low. This research emphasizes the urgent need for regulatory reform, particularly in strengthening the recognition of electronic evidence under Indonesian law, and promoting legal literacy to encourage society to document agreements more effectively. By highlighting both theoretical and practical dimensions, the study contributes to the development of contract law discourse in Indonesia and provides policy recommendations to improve the balance of legal protection between parties in contractual relations.